Ol' Mama Squirrel - Stein, David Ezra (Nancy Paulsen Books, 2013)
Ol' Mama Squirrel has raised many babies and kept them all safe from predators, but she may have met her match when a determined grizzly bear threatens to eat her entire family tree.